Reasoning, logic, and category mistakes - Castro-Manzano, J. Martín (Aufklärung: journal of philosophy, 2017)
In this contribution we sketch a propositional logical system designed to represent reasoning with philosophical categories. This should be of relative interest, at least, for two reasons. In first place, the proposed system attempts to formalize the notion of category mistake; and, in second place, the system provides a formal alternative to regulate reasoning involving categories, since the propositional systems typically used to represent reasoning are unable to do that, thus allowing the introduction of category mistakes.